Impact of Option Length on Students' Mathematics Achievement in Command Secondary Schools in Nigeria - D. O. Tobih; A. M. Izang (University of Sofia, 2020)
The study adopted Causal Comparative research design. A sample of 270 students was selected from five schools using stratified sampling technique. Three instruments: Three Options Mathematics Achievement Test (TOMAT) (r = 0.76), Four Options Mathematics Achievement Test (FOMAT) (r = 0.84) and Five Options Mathematics Achievement Test (FIOMAT) (r = 0.70), were used for data collection. 3-way ANOVA was used to test the hypotheses at 0.05 level of significance. Results of the analyses showed a significant effect of option length on students' Mathematic achievement (F2, 267 = 19.652; P (0.00) < .05); no significant effect of gender on students' Mathematics achievement (F1, 267 = .732; P (.482) > .05); a significant effect of field of study on students' Mathematics achievement (F2, 267 = 12.623; P (.000) < .05), and a significant effect of option length and gender on students' Mathematics achievement (F2, 267 = 3.504; P (.032) < .05). It is therefore recommended that teachers of Mathematics should endeavor to devote more time and expertise to test construction, especially in the area of option length as this goes a long way in influencing students' achievement in the subject.